Complement Factor I Mutation May Contribute to Development of Thrombotic Microangiopathy in Lupus Nephritis - Tseng, Min-Hua; Fan, Wen-Lang; Liu, Hsuan; Yang, Chia-Yu; Ding, Jhao-Jhuang; Lee, Hwei-Jen; Huang, Shih-Ming; Lin, Shih-Hua; Huang, Jing-Long (Frontiers in Medicine, 2021)
Objective. Renal thrombotic microangiopathy (TMA) is associated with complement overactivation and poor outcome in patients with lupus nephritis. The role of genetic makeup of complement system in these patients remains to be elucidated. Methods. The clinical and laboratory characteristics of patients with lupus nephritis (LN) during 2010 to 2017 were retrospectively analyzed. LN patients with renal TMA and condition-matched LN patients without renal TMA were studied. Twenty normal subjects were also enrolled for comparison. Whole exome sequence followed by Sanger sequence was used in our study cohort. Results. Eight patients with renal TMA and 8 condition-matched patients were enrolled from 100 LN patients with mean age 11.2±2.0 years. Compared with condition-matched LN patients, LN patients with renal TMA exhibited statistically higher serum urea. Although most patients with renal TMA responded to plasma exchange, they had significantly higher relapse rate of nephritis, lower remission rate, and higher risk of end stage renal disease and mortality. Compared with patients without renal TMA and normal subjects, those with renal TMA had significantly lower serum CFH and plasma ADAMTS13 activity. Molecular analysis of all LN patients uncovered that three patients with renal TMA harbored mutations, two missense and nonsense, on CFI and CFHR2. The nonsense mutation, E302X, on CFI may impair its interaction C3b/CFH complex by lost of the heavy chain of CFI on simulation model. Conclusion. In addition to low serum CFH level and plasma ADAMTS13 activity, defects in genes responsible for complement regulatory proteins may contribute to the development of renal TMA in patients with LN.